Potentials of natural polymers as nanomaterials for pharmaceutical drugs delivery (2013)
During the last decades, pharmaceutical technology has taken advantage of the advent of nanotechnology for its application in four broad areas of the pharmaceutical industry: drug delivery, diagnostic products, biomarker discovery and product packaging. Of all the potential pharmaceutical applications of nanotechnology, drug delivery is currently the most developed and seems to be the most promising for the long-term. Of great advantage is the concept and ability to manipulate molecules and supramolecular structures to produce drug delivery devices with great potential for improving the efficacy of drug delivery systems. Polymeric nanoparticles are colloidal carriers which usually consist of synthetic, semi-synthetic or natural polymers, and depending on the materials used and their manufacturing methods, nanoparticles can adopt diverse shapes and sizes with distinct properties. Natural polymers such as gelatin, albumin, alginate and chitosan have great potentials because of their inherent properties such as biocompatibility, non-immunogenicity, non-toxicity and biodegradability. In addition, they can be subjected to physical and chemical modifications to alter their physic-chemical properties resulting in a wide range of functional properties that may permit their application as polymers for the formulation of nanoparticles. Moreover, they have been found to issues and relatively inexpensive when compared to the synthetic polymers. This paper is a review of some natural polymers that have shown promise as biodegradable polymers for the formulation of nanoparticulate drug delivery system.